Epidemiology and management burden of invasive fungal infections after autologous hematopoietic stem cell transplantation: 10‐year experience at a European Pediatric Cancer Center. Issue 10 (18th August 2019) - Linke, Christina; Tragiannidis, Athanasios; Ahlmann, Martina; Fröhlich, Birgit; Wältermann, Maria; Burkhardt, Birgit; Rossig, Claudia; Groll, Andreas H.
Summary: Background: Autologous hematopoietic stem cell transplantation (HSCT) carries risks of infectious morbidity. We analysed epidemiology and management burden associated with invasive fungal diseases (IFDs) in children and adolescents undergoing autologous HSCT. Methods: In a retrospective, single‐centre observational study, epidemiology and management burden associated with IFDs were analysed in all paediatric cancer patients who underwent autologous HSCT between 2005 and 2014. Clinical, radiographic and microbiological data were assessed up to 100 days post‐transplant. The primary endpoint was the incidence of proven, probable and possible IFDs. Further endpoints included the use of systemic antifungal agents for prevention and management of IFDs; infectious and non‐infectious comorbidities; and survival until day + 100. Results: Of 95 patients (median age: 8 years; r, 0.75‐20) underwent 103 HSCT procedures for solid tumours (92) or lymphoma (11). Primary antifungal prophylaxis was administered in 49 procedures (47.5%). No single case of proven/probable IFD was diagnosed. Nine cases (8.7%) fulfilled criteria of possible pulmonary mould infection and received treatment for a median of 14 days (r, 7‐35). In an additional 12 procedures, empiric antifungal therapy with mould active agents was given for a median of 8 days (r, 3‐105). Microbiologically documented non‐fungal infections were observed in 17 procedures, and five patients were transferred to the ICU. There was one death from biopsy documented toxic endothelial damage at day 83 post‐transplant. Conclusions: Autologous HSCT for solid tumours or lymphoma was associated with low morbidity from IFDs. However, utilisation of systemic antifungal agents for prevention and management of suspected IFDs was considerable.